ChemInform Abstract: Reaction of Arynes with Vinylogous Amides: Nucleophilic Addition to the ortho‐Quinodimethide Intermediate. Issue 4 (28th January 2014) - Li, Ran; Wang, Xuemei; Wei, Zhibin; Wu, Chunrui; Shi, Feng
Abstract Vinylogous amides react with arynes in a [2 + 2] cycloaddition/ring‐opening sequence to furnish an electronically instable ortho‐quinodimethide intermediate.